Association of Lipoprotein(a)-Associated Mortality and the Estimated Glomerular Filtration Rate Level in Patients Undergoing Coronary Angiography: A 51,500 Cohort Study - Huang, Zhidong; Yang, Yanfang; Lu, Jin; Liang, Jingjing; He, Yibo; Yu, Yaren; Huang, Haozhang; Li, Qiang; Wang, Bo; Li, Shanggang; Yan, Zelin; Xu, Danyuan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: High lipoprotein(a) is associated with poor prognosis in patients at high risk for cardiovascular disease. Renal function based on the estimated glomerular filtration rate (eGFR) is a potential risk factor for the change of lipoprotein(a). However, the regulatory effect of eGFR stratification on lipoprotein(a)-associated mortality has not been adequately addressed. Methods: 51,500 patients who underwent coronary angiography (CAG) or percutaneous coronary intervention (PCI) were included from the Cardiorenal ImprovemeNt (CIN) study (ClinicalTrials.gov NCT04407936). These patients were grouped according to lipoprotein(a) quartiles (Q1 to Q4) stratified by eGFR categories (<60 and ≥60 mL/min/1.73m²). Cox regression models were used to estimate hazard ratios (HR) for mortality across combined eGFR and lipoprotein(a) categories. Results: The mean age of the study population was 62.3±10.6 years, 31.3% were female (n=16,112). During a median follow-up of 5.0 years (interquartile range: 3.0 to 7.6 years), 13.0% (n=6,695) of patients died. Compared with lipoprotein(a) Q1, lipoprotein(a) Q2-Q4 was associated with 10% increased adjusted risk of death in all patients (HR: 1.10 [95% CI: 1.03-1.17]), and was strongly associated with about 23% increased adjusted risk of death in patients with eGFR <60 mL/min/1.73m² (HR: 1.23 [95% CI: 1.08-1.39]), while such association was not significant in patients with eGFR ≥60 mL/min/1.73m² (HR: 1.05 [95% CI: 0.97-1.13]). P for interaction between lipoprotein(a) (Q1 vs. Q2–Q4) and eGFR (≥60 vs. eGFR <60 mL/min/1.73m²) on all-cause mortality was 0.019. Conclusions: Elevated lipoprotein(a) was associated with increased risk of all-cause mortality and such an association was modified by the baseline eGFR in CAG patients. More attention should be paid to the patients with reduced eGFR and elevated lipoprotein(a), and the appropriate lipoprotein(a) intervention is required.